2011
DOI: 10.1051/0004-6361/201015383
|View full text |Cite
|
Sign up to set email alerts
|

A Sino-Germanλ6 cm polarization survey of the Galactic plane

Abstract: Aims. We study polarized short-wavelength emission from the inner Galaxy, which is nearly invisible at long wavelengths because of depolarization. We attempt to obtain information on the diffuse continuum emission at short wavelengths to help us to separate Galactic thermal and non-thermal components. Methods. We conducted a total intensity and polarization survey of the Galactic plane at λ6 cm using the Urumqi 25 m telescope for the Galactic longitude range of 10 • ≤ l ≤ 60 • and the Galactic latitude range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 45 publications
4
87
0
Order By: Relevance
“…In this paper, we present new λ6 cm and λ11 cm observations of CTA 1, which is one of the targets of a campaign to map large northern sky SNRs at λ6 cm. This project is part of the Sino-German λ6 cm polarisation survey of the Galactic plane Gao et al 2010;Sun et al 2011;Xiao et al 2011;Gao et al 2011). Results on some large SNRs have been already reported, such as G65.2+5.7 (Xiao et al 2009), the Cygnus Loop (Sun et al 2006), HB 3 (Shi et al 2008), G156.2+5.7 (Xu et al 2007), and S 147 (Xiao et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…In this paper, we present new λ6 cm and λ11 cm observations of CTA 1, which is one of the targets of a campaign to map large northern sky SNRs at λ6 cm. This project is part of the Sino-German λ6 cm polarisation survey of the Galactic plane Gao et al 2010;Sun et al 2011;Xiao et al 2011;Gao et al 2011). Results on some large SNRs have been already reported, such as G65.2+5.7 (Xiao et al 2009), the Cygnus Loop (Sun et al 2006), HB 3 (Shi et al 2008), G156.2+5.7 (Xu et al 2007), and S 147 (Xiao et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…There are also some individual discoveries, although not many. The SinoGerman λ6 cm polarization survey of the Galactic plane 1 (Sun et al 2007(Sun et al , 2011a; Gao et al 2010;Xiao et al 2011) conducted by the Urumqi 25-m radio telescope provides a good hunting ground for discovering new Galactic SNRs. Gao et al (2011) identified two new faint SNRs G25.1−2.3 and G178.2−4.2.…”
Section: Introductionmentioning
confidence: 99%
“…It covers 10 • ≤ ≤ 230 • in Galactic longitude and |b| ≤ 5 • in Galactic latitude Gao et al 2010;Sun et al 2011;Xiao et al 2011). The Urumqi λ6 cm polarization system is suitable for observations of large and faint SNRs.…”
Section: Introductionmentioning
confidence: 99%